Measuring women’s empowerment and gender equality in national statistical systems and national agri-food policy processes - Ragasa, Catherine (International Food Policy Research Institute, 2023)
This session will present four new measurement tools, indices, or scorecards to help governments and their partners measure and track progress in women’s empowerment and gender equality in national agri-food and climate policy processes and national statistical systems. These tools fill an important knowledge and measurement gap and aim to identify entry points and influence policy dialogues around accountability towards gender, nutrition and climate-resilience goals. The first tool is the Women’s Empowerment in Agrifood System Governance (WEAGov) assessment tool that measures gender consideration, women’s inclusion and women’s influence in three stages of the agri-food policy process—design, implementation and evaluation—via policy and institutional mapping, policy content analysis, organizational and expert surveys and focus group discussions. The second tool is the Gender in Agriculture Policy tool (GaPo) used to assess 83 main agricultural policies of low, lower-middle and upper-middle-income economies. The third tool is the Women’s Empowerment Metric for National Statistical Systems (WEMNS), which captures indicators and survey questions to help measure women’s empowerment in national statistical systems. The fourth tool is a national scorecard to support genderresponsive and nutrition-sensitive monitoring of climate policies, investments and actions. The scorecard is comprised of several domains reflective of policy decisions (e.g., level of gender integration in policy design); policy processes (e.g., women’s leadership and participation in policy design and implementation); and outcome indicators (e.g., women’s access to key resources and services). The four presentations will include the details of the measurement and results from different country pilots.